Pengaruh Penyaluran Dana ZIS dan Tingkat Inflasi Terhadap Pertumbuhan Ekonomi di Provinsi Bengkulu Periode 2021-2024 - Annisa; Asnaini; Nonie Afrianty (Universitas Muhammadiyah Surabaya, 2026)
This study aims to analyze the effect of ZIS fund distribution and the inflation rate on economic growth in Bengkulu Province for the 2021-2024 period. The research method used a quantitative approach with multiple linear regression techniques. The data used were secondary data collected from the National Zakat Agency (BAZNAS) of Bengkulu Province and inflation rate data from the Central Statistics Agency (BPS) of Bengkulu Province for the 2021-2024 period, covering monthly data for the entire province. The results show that ZIS fund distribution (X1) has a negative and significant effect on economic growth in Bengkulu Province, and the inflation rate (X2) has no significant effect on economic growth in Bengkulu Province. Meanwhile, ZIS fund distribution and the inflation rate together have a significant effect on economic growth in Bengkulu Province for the 2021-2024 period.